If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2m + -30 = -8(1 + -3m) Reorder the terms: -30 + 2m = -8(1 + -3m) -30 + 2m = (1 * -8 + -3m * -8) -30 + 2m = (-8 + 24m) Solving -30 + 2m = -8 + 24m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-24m' to each side of the equation. -30 + 2m + -24m = -8 + 24m + -24m Combine like terms: 2m + -24m = -22m -30 + -22m = -8 + 24m + -24m Combine like terms: 24m + -24m = 0 -30 + -22m = -8 + 0 -30 + -22m = -8 Add '30' to each side of the equation. -30 + 30 + -22m = -8 + 30 Combine like terms: -30 + 30 = 0 0 + -22m = -8 + 30 -22m = -8 + 30 Combine like terms: -8 + 30 = 22 -22m = 22 Divide each side by '-22'. m = -1 Simplifying m = -1
| 10x+4y=134 | | 20x-5=75 | | 20x-5=50 | | 20x-5=100 | | 34-3x=-2-5(x-4) | | x/12=5/13 | | 24-3x=-2-5(x-4) | | 8m-6n+2m+5n= | | 1/4x-5/6=1/4 | | (11x-(5/4)x/(3/2) | | 60x+20y=3600 | | (14b^7)/(7b^14)= | | 2x+12=1024 | | (14b^7)(7b^14)= | | 5x+3y=9.5 | | y=-8x-16x+280 | | 5(-2x+3)+4x-5=-50 | | 4(-4x+3)-2x+1=85 | | 2x^2+28x+98=24 | | 12x-2(8+5x)=12-11x | | 168=106-w | | x^2-3x=6x | | 4s^2=8s+9 | | xy-3x=-4 | | -m^2+3m-3=2 | | (3x^4)(2x^7)= | | 8x^2-27x-20= | | 4(y+2)-5y=y+12 | | (7^-1z^-3x)(5z^3x^4)^-2/4z^-3x^-3)^2 | | 3y^2-17xy-6x^2= | | -4a^2+3a-5=2 | | y=25x+30y |